2019
DOI: 10.3390/nu11122897
|View full text |Cite
|
Sign up to set email alerts
|

High Hydration Factor in Older Hispanic-American Adults: Possible Implications for Accurate Body Composition Estimates

Abstract: Age- and obesity-related body composition changes could influence the hydration factor (HF) and, as a result, body composition estimates derived from hydrometry. The aim of the present study was to compare the HF in older Hispanic-American adults to some published values. This cross-sectional study included a sample of 412 subjects, men and women, aged ≥60 years from northern Mexico. HF values were calculated based on the ratio of total body water-using the deuterium dilution technique-to fat-free mass, derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As mentioned above, confirmed subjects with diseases present alterations at the tissular level, which is reflected in their PhA values [ 8 , 18 , 19 ]. Particularly, PhA is influenced by age, BMI and sex, due to the variations in total body water (TBW) content [ 9 , 30 ]. It is well established that PhA is based on the resistance and reactance of the tissues, with TBW being the main component that influences these parameters [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, confirmed subjects with diseases present alterations at the tissular level, which is reflected in their PhA values [ 8 , 18 , 19 ]. Particularly, PhA is influenced by age, BMI and sex, due to the variations in total body water (TBW) content [ 9 , 30 ]. It is well established that PhA is based on the resistance and reactance of the tissues, with TBW being the main component that influences these parameters [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that PhA is based on the resistance and reactance of the tissues, with TBW being the main component that influences these parameters [ 31 ]. It has been reported that TBW decreases with age, increases with the presence of obesity, and women have more liters of TWB compared with men [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%